Analysis Of Urban Design Dimensions in A Cultural Heritage Area (Case Study: Kotabaru Area, Yogyakarta City) - Hilba Yoga Pratama; Agung Budi Sardjono (Journal of Architecture & Environment, 2023)
The design concept for the Kotabaru area was designed to resemble the hometown of the Dutch, as if the area had become a second hometown for the Dutch who lived in Yogyakarta during the colonial period. Kotabaru was formerly called Nieuwe Wijk, designed with the Garden City concept by a Dutch architect named Thomas Karsteen. The research aims to analyze the dimensions of urban design in the cultural heritage area in Kotabaru Yogyakarta. This area has very important socio-cultural values and is part of a city identity. However, the growth and changes in urbanization have had an impact on the quality of urban planning. The research method used is descriptive qualitative. Data were collected through field observations, documentation studies, and interviews. The research location is in Kotabaru Yogyakarta, focusing on cultural heritage areas and historic buildings. The analysis includes elements of architecture, spatial planning, land use, regional zoning, and relations with local socio-culture. The research results reveal dimensions of city design, including morphological dimensions, social dimensions, perceptual dimensions, visual dimensions, functional dimensions, temporal dimensions related to elements in the Kotabaru Yogyakarta cultural heritage area.